17O solid‐state NMR at ultrahigh magnetic field of 35.2 T: Resolution of inequivalent oxygen sites in different phases of MOF MIL‐53(Al). (8th February 2021) - Martins, Vinicius; Xu, Jun; Hung, Ivan; Gan, Zhehong; Gervais, Christel; Bonhomme, Christian; Huang, Yining
Abstract: MIL‐53(Al) is a member of the most extensively studied metal–organic framework (MOF) families owing to its "flexible" framework and superior stability. 17 O solid‐state NMR (SSNMR) spectroscopy is an ideal site‐specific characterization tool as it probes local oxygen environments. Because oxygen local structure is often altered during phase change, 17 O SSNMR can be used to follow phase transitions. However, 17 O is a challenging nucleus to study via SSNMR due to its low sensitivity and resolution arising from the very low natural abundance of 17 O isotope and its quadrupolar nature. In this work, we describe that by using 17 O isotopic enrichment and performing 17 O SSNMR experiments at an ultrahigh magnetic field of 35.2 T, all chemically and crystallographically inequivalent oxygen sites in two representative MIL‐53(Al) (as‐made and water adsorbed) phases can be completely resolved. The number of signals in each phase is consistent with that predicted from the space group refined from powder X‐ray diffraction data. The 17 O 1D magic‐angle spinning (MAS) and 2D triple‐quantum MAS (3QMAS) spectra at 35.2 T furnish fine information about the host–guest interactions and the structural changes associated with phase transition. The ability to completely resolve multiple chemically and crystallographically inequivalent oxygen sites in MOFs at very high magnetic field, as illustrated in this work, significantly enhances the potential for using the NMR crystallography approach to determine crystal structures of new MOFs and verify the structures of existing MOFs obtained from refining powder X‐ray diffraction data. Abstract : Three different phases of flexible MOF MIL‐53(Al) have been examined by 17 O SSNMR at an ultrahigh magnetic field strength of 35.2 T. All chemically and crystallographically inequivalent oxygen sites have been resolved for each phase. The very high 17 O spectral resolution and sensitivity achieved at 35.2 T allow us to extract fine information on local oxygen environments and host–guest interactions in each phase.